PROPHYLAXIS EFFICACY OF THE PREPARATION BASED ON “FAGODENT” AND “TRAUMEL S” IN DENTAL IMPLANTOLOGY - Ismatov Farrukh Aslidinovich; Bekmurodov Lukmon Rustamovich; Ibodov Ulmas Ergash ugli (Research Focus International Scientific Journal, 2025)
This article studies the prophylactic efficacy of the preparations “Fagodent” and “Traumel S” in dental implantology. These preparations are mainly used to reduce inflammation, infection and pain after the implantation procedure, as well as to accelerate the recovery of injured tissues. “Fagodent” is characterized by its plant-based antibacterial and anti-inflammatory effect, while “Traumel S” supports the immune system through a number of its properties and accelerates recovery. The article shows the clinical efficacy of both preparations and analyzes how their combined use helps in the successful implementation of the implantation procedure.